A second look at partisanship's effect on receptivity to social pressure to vote. (2nd January 2019) - Matland, Richard E.; Murray, Gregg R.
ABSTRACT: Social pressure can exert a powerful, but sometimes counterproductive, influence on compliance with the social norm of voting. Scholars have tested several implicit social pressure techniques to reduce negative reactions to these methods. Among the most innovative is the use of 'watching eyes' in voter mobilization messages. Using three large randomized field experiments, this study attempts to reproduce Panagopoulos and van der Linden's finding that political partisanship moderates the effect of watching eyes messages on voter turnout. Our findings diverge from previous findings statistically and substantively and indicate partisanship may have limited influence on the effectiveness of watching eyes in mobilizing voters.